Caracterização e fatores de risco para óbito e recidiva da leishmaniose visceral em pacientes coinfectados por HIV - Henn, Guilherme Alves de Lima (2016)
Visceral Leishmaniasis (VL) is endemic in 70 countries, including Brazil, and Ceará stands out for the large number of reported cases. It is known that L. infantum infection accelerates progression to AIDS while immunosuppression caused by HIV allows uncontrolled replication of the parasite. However, it is not clear what factors are associated with unfavorable outcomes for coinfection. This study aimed to describe clinical and laboratory presentation with VL-HIV coinfection and to identify potential factors associated with relapse and death. VL patients were enrolled from São José Hospital, Fortaleza-CE, between July 2010 and December 2013. Epidemiological, clinical, laboratory and treatment variables of patients with VL-HIV coinfection were compared with a control group of patients with non-coinfected VL. Outcomes and associated factors for relapse and death after one year of treatment were evaluated for the HIV-positive group, through retrospective cohort. Eighty-one HIV-positive patients and 365 HIV-negative controls were included. It was found that individuals with VL coinfected by HIV were licit and illicit drug-users more often; they presented less commonly with fever, malaise, anorexia, jaundice and edema and had more diarrhea; anemia and lymphopenia were more pronounced and AST and conjugated bilirubin were lower. Anti-rK39 sensitivity was lower in this group. HIV infection increased 26 times the chance of relapse and the first episode of kala-azar appeared to be the critical moment to modify the natural history of coinfection. Symptoms for more than six months, diarrhea and T CD4 cell count less than 200/mm3 were associated with greater chance for relapse, while hypoalbuminemia, thrombocytopenia, and oral/esophageal candidiasis or tuberculosis previous or concomitant to VL were associated with death. Smoking and residence in the countryside were also associated with occurrence of unfavorable outcomes. T CD4 cell count above 350/mm3 and use of amphotericin B deoxycholate were protective factors. It is recommended to increase clinical suspicion for VL in HIV-infected individuals in order to diagnose and treat them as early as possible and avoid progression to relapse or death.